ضمانات الحيدة - المفرجي، أحمد خورشيد حميدي; الجاف، فرات رستم أمين; أمين، جوان ناصح (جامعة كركوك - كلية القانون والعلوم السياسية, 2020)
إن القانون العراقي اشترط أن يكون أحد أعضاء اللجنة التحقيقية حاصلا على شهادة أولية في القانون ليحقق الحياد والضمان للموظف، وبضمان الحيدة يجب أن لا يكون أي من أعضاء اللجنة التحقيقية له سلطة فرض العقوبة على الموظف، أي لا يجوز أن يجمع بين سلطة الاتهام والحكم، وإذا كان النظام المطبق في العراق هو النظام الرئاسي حيث يعطى للرئيس الإداري سلطة التحقيق وفرض العقوبة فلابد من البحث عن ضمانات تجاه هذه السلطات، لذلك تناولنا في هذا البحث أهم الضمانات الكفيلة لتحقيق الحيدة في مرحلة التحقيق ومرحلة ما بعد فرض العقوبة.
Iraqi law stipulated that one of the members of the investigation committee must have a preliminary certificate in the law to achieve neutrality and security for the employee, and by guaranteeing impartiality, none of the members of the investigation committee should have the authority to impose the penalty on the employee, that is, it is not permissible to combine the authority of accusation and judgment, and if he The system applied in Iraq is the presidential system, where the administrative head is given the investigation and the imposition of the punishment, so we must search for guarantees against these authorities. Therefore, we discussed in this research the most important guarantees to achieve impartiality in the investigation stage and the post-imposition of punishment.
Keywords: القوانين والتشريعات -- القانون المرافعات -- السلطة القضائية -- الحياد